ANALYSIS OF THE DIFFICULTIES OF PHONEME-GRAPHEME CORRESPONDENCE IN READING ENGLISH FOR GRADE VI STUDENTS AT ELEMENTARY SCHOOL 106166 MARINDAL 2 - Hutapea, Indah Jesica; Girsang, Asaria Semaya; Nainggolan, Fadhillah Azzahra; Rambe, Rizki Muda Ananda; Simanjuntak, Eva Betty; Nasution, Dea Yuanita (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2026)
Mastering  reading  skills  is  a  crucial  foundation  in  learning  English  as  a  Foreign Language (EFL), particularly at the elementary school level. At SDN 106166 Marindal 2, sixth-grade  students  are  challenged  to  master  vocabulary  and  pronunciation  as  a foundation. However, this learning process faces specific obstacles directly related to the linguistic systems of the two languages being studied. This  research  is  urgently  needed  to comprehensively  analyze  the  difficulties  in  phoneme-grapheme  correspondence  and formulate pedagogical recommendations that focus on the methodological transition (from repetition to phonics) and a student-centered approach, which has been proven effective in addressing reading and pronunciation difficulties in sixth-grade students at SDN 106166 Marindal 2.